Infusion of Human Albumin on Acute Pancreatitis Therapy: New Tricks for Old Dog? - Ma, Yifei; Yan, Tianao; Xu, Fengshuo; Ding, Jiachun; Yang, Bao; Ma, Qingyong; Wu, Zheng; Lyu, Jun; Wang, Zheng (Frontiers in Pharmacology, 2022)
Objective: Human serum albumin (HSA) infusion is a common administration on acute pancreatitis therapy in the Intensive Care Unit (ICU), but its actual association with patients' outcomes has not been confirmed. The study is aimed to determine whether the in-hospital prognosis of ICU patients with acute pancreatitis could benefit from HSA. Methods: 950 acute pancreatitis patients diagnosed in 2008-2019 were extracted from the MIMIC-IV database as our primary study cohort. The primary outcome was in-hospital mortality. We also performed an external validation with a cohort of 104 acute pancreatitis patients after PSM matching from the eICU database. Results: In MIMIC-IV, 228 acute pancreatitis patients received HSA infusion (Alb group) during their hospitalization, while 722 patients did not (non-Alb group). Patients in the Alb group presented a poorer survival curve than the non-Alb group, while this difference disappeared after PSM or IPTW matching (log-rank test: PSM: p = 0.660, IPTW: p = 0.760). After including covariates, no association was found between HSA infusion and patients' in-hospital mortality before and after matching (original cohort: HR: 1.00, 95% CI: 0.66–1.52, p = 0.998). HSA infusion also did not benefit patients' 28-day or ICU mortality, while it was significantly associated with a longer duration of hospital and ICU. In addition, the initial serum albumin levels, infections, the total amount, or the initial timing of infusion did not affect the conclusion. Similarly, in the eICU cohort, HSA infusion was still not a beneficial prognostic factor for patients' in-hospital prognosis ( p = 0.087). Conclusion: Intravenous human serum albumin infusion could not benefit acute pancreatitis patients' in-hospital prognosis and was associated with prolonged hospital and ICU duration.